BATASAN DAN PEMBERIAN INFORMASI MEDIS TERHADAP PIHAK KETIGA DI RUMAH SAKIT HERMINA ARCAMANIK TAHUN 2021 - Nabilla Nur Hasna; Nanda Novyadianti; Irda sari (Media Bina Ilmiah, 2022)
Health care facilities are responsible for protecting the health information contained in the medical record to the possibility lost, damaged, forgery and unauthorized access. Overall, security (security), privacy (privacy), confidentiality (confidentiality) and safety (safety) is a device that fortify the information in the medical record. The purpose of this study is to know the description of the restrictions and the provision of medical information to a 3rd-party in the Hospital Hermina Arcamanik.The research method in this research using the method of the research descriptive aims to make an overview of the restrictions and the provision of medical information in the Hospital Hermina Arcamanik about a situation objectively in the Hospital Hermina Arcamanik. in ensuring the legal aspects of confidentiality of patient medical records.Sample in this research is partly drawn from the whole of the object under study and is considered to represent the whole population .The population of this study is a limitation and provision of medical information in the warrant to a third party. Engineering sampling is by way of the technique of total sampling. From the research result shows that the parties involved in the process of release of medical information of the patient Hospital Hermina Arcamanik is Training, Sub Bag, Medical Records, Doctors/Medical Personnel and officers of the room.Preferably held socialization about the procedure remain regarding the patient to the officer record medical or parties involved in the provision of information to the patient's medical.Use written permission in any release of information medical records of patients has not been accomplished with optimal.